1999
DOI: 10.1063/1.882909
|View full text |Cite
|
Sign up to set email alerts
|

How the Laser Happened: Adventures of a Scientist

Abstract: Like 64 submit reddit Exclusive excerpt from Nobel Laureate Charles H. Townes's book, How the Laser Happened: Adventures of a Scientist (published by Oxford University Press in 2002). In this book, Townes provides a highly personal look at some of the leading events in twentieth-century physics. Townes was inventor of the maser, of which the laser is one example; an originator of spectroscopy using microwaves; and a pioneer in the study of gas clouds in galaxies and around stars. Throughout his career he has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…The paper then dimensionalizes innovation impact by introducing the terms reach, significance, and paradigm change that can be used to identify enabling and progressive innovations. The identified dimensions of reach, impact, and paradigm change stem from the integration of literature that focuses on describing societal impact across fields such as government, business, science, technology, and engineering [9][10][11][12][13][14][15][16][17][18] and in-depth reviews of historical innovations [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] to establish new links between impact and innovation. Emphasis is placed on reviewing cases that do not have a commercial orientation to underscore the importance of becoming effective at describing innovation regardless of the nature of the innovative activity (e.g., research, development, commercialization).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The paper then dimensionalizes innovation impact by introducing the terms reach, significance, and paradigm change that can be used to identify enabling and progressive innovations. The identified dimensions of reach, impact, and paradigm change stem from the integration of literature that focuses on describing societal impact across fields such as government, business, science, technology, and engineering [9][10][11][12][13][14][15][16][17][18] and in-depth reviews of historical innovations [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] to establish new links between impact and innovation. Emphasis is placed on reviewing cases that do not have a commercial orientation to underscore the importance of becoming effective at describing innovation regardless of the nature of the innovative activity (e.g., research, development, commercialization).…”
Section: Methodsmentioning
confidence: 99%
“…Some innovations, for instance, lasers 30 or the C programming language, are inherently of higher impact than ideas with a purely commercial scope (e.g., a new laser application, or a novel software). Thus, a language to characterize/classify ideas based on impact -such as the one put forward in this paper -can help evaluate and prioritize ideas with innovative potential.…”
Section: Patterns Of Innovation Based On Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…Several books in recent years have related that history from several points of view. [1][2][3][4][5] Among the authors are Theodore Maiman, who first observed laser action in crystalline pink ruby, and Charles Townes, who invented the original ammonia maser and shared the 1964 Nobel Prize in Physics with Nicolay Basov and Aleksandr Prokhorov for the "maser-laser principle." But apart from our publication of scientific papers at the time, only our colleague Arthur Schawlow has left an account of the work at Bell Labs in the summer of 1960 that led to the creation of the first ruby laser.…”
mentioning
confidence: 99%